POTENSI AIR PERASAN BELIMBING WULUH (Averrhoa bilimbi L) SEBAGAI BAHAN ALTERNATIF DENTIN CONDITIONER DALAM PERAWATAN KONSERVASI GIGI (IN-VITRO) - Lestari, Sri; Arifin, Zainal; W, Ekiyantini (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Preparation level prior to conduct dental filling results in smear layer. When smear layer is too thick, it will disturb the adhesion of restoration material to cavity wall, therefore it needs cleansing using dentin conditioner. One of cleansing materials for smear layer is acid with low concentration like citrate acid, hydrogen peroxide, and 10% of polyacrilate acid (Sutrisno, 2005). The use of natural materials in dental practice is an alternative and may minimize the side efect, one of them is belimbing wuluh (Averrhoa bilimbi L). This study is experimental laboratory aimed at analysing the potential of cleansing force of belimbing wuluh (Averrhoa bilimbi L) juice on the smear layer of cavity wall of tooth prepared. Ten samples of incisive teeth of cows were prepared with circle-shaped class 1 cavity design with 5 mm in diameter, 2,5 mm in depth in one third from the center of dental labial surface. Subsequently, 5 samples were polished with 10% of poliacrylic acid, the other 5 samples were polished 100% of belimbing wuluh juice, allowed for 10 seconds and irrigated with sterile aquades and dried. The samples were examined for their cleanliness from smear layer using SEM with 5000x magnifying. The result showed average value of cleanliness of the cavity bottom from smear applied with 10 % of polyacrilate acid was lower compared to the group with 100% of belimbing wuluh juice. Statistically, it showed a significant difference between the control group (10 % of polyacrilate acid) and treatment group (100% of belimbing wuluh juice). In conclusion, 100% of belimbing wuluh juicen has potential as dentin conditioner.